INTERAKSI ETNIS TIONGHOA MUSLIM DAN NON MUSLIM DI KOTA PADANG PROPINSI SUMATERA BARAT - Hanura Rusli; Rois Leonard Arios (Kementerian Pendidikan dan Kebudayaan, 2020)
Ethnic Chinese as one of the ethnic minorities in Padang City is divided into two major groups, namely Muslim Chinese and non-Muslim. This grouping occurred because Muslim Chinese were considered unable to follow Chinese culture. This grouping often becomes an obstacle in the interactions between them. Research is based on the assumption that differences in religious background are a factor that influences individual interactions with other individuals or groups. However, in its development, religious differences are no longer a barrier to interaction between fellow ethnic Chinese. The purpose of this study was to answer the research question, namely how the forms of interaction and the basis of the interactions carried out by Muslim and non-Muslim Chinese ethnicities. To analyze the problem using the perspective of action theory by Parson. The research was conducted using a qualitative method by collecting data through interviews, literature study, and observations of involvement in social and cultural activities of the Chinese ethnic group. Data were analyzed by ethnographic method. The results showed that the interaction of Chinese Muslims and non-Muslims was associative in the form of cooperation and involvement in various social activities. This interaction is a form of openness of each group to change and awareness of the need to interact with each other because of the feeling of a cultural background. This is also supported by the existence of the HBT, HTT, and PITI organizations in Padang City.